Stability in a Closed Economy and in the Foreign Exchange Market, and the Redistributive Effect of Price Changes - Spraos, John (Review of Economic Studies, 1957)
Journal Article Stability in a Closed Economy and in the Foreign Exchange Market, and the Redistributive Effect of Price Changes Get access John Spraos John Spraos University of Sheffield Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 3, June 1957, Pages 161–176, https://doi.org/10.2307/2296065 Published: 01 June 1957